2011
DOI: 10.1007/s12232-011-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

The political determinants of liberalization: do ideological cleavages still matter?

Abstract: We investigate the political determinants of liberalization in OECD network industries, performing a panel estimation over 30 years, through the largest and most updated sample available. Our results contrast with the traditional wisdom according to which right-wing governments do promote market-oriented policies more intensively than left-wing ones. Our findings reveal a neglected role of the so-called neoliberalism in promoting left-wing market-oriented policy. As a result, we claim that ideological cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Additionally, Potrafke () found that relatively more pro‐market governments were associated with deregulation of key industries across the OECD including energy, transportation, and communication. However, Belloc and Nicita () contradict this finding, showing that in a panel of OECD countries relatively more left‐wing governments are more active in advancing market liberalization.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Additionally, Potrafke () found that relatively more pro‐market governments were associated with deregulation of key industries across the OECD including energy, transportation, and communication. However, Belloc and Nicita () contradict this finding, showing that in a panel of OECD countries relatively more left‐wing governments are more active in advancing market liberalization.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Our econometric analysis provides a robust framework to ascertain whether rightist ideology actually drives privatization choices of governments, or if it is, instead, neutral as for other public policies (Belloc and Nicita, 2011). We have included 1-year lagged public ownership and entry barriers to market levels along with public finance indicators in a regression model for privatization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Potrafke (2010) as well as Smith and Urpelainen (2016) find that right-wing parties also favour product market deregulation compared with leftist parties. However, Belloc and Nicita (2011) find that ideological cleavages play no important role in the regulation of network industries, as governments under control of both left and right-wing parties pursued deregulation of such industries (compared with 'centre' governments). Overall, however, empirical evidence suggests that government ideology shapes regulation: right-wing parties more actively pursue deregulation and privatization, as opposed to left-wing parties that tend to limit economic freedom.…”
Section: Hypothesizing On Partisan Effects On Government Activity mentioning
confidence: 92%